1997
DOI: 10.1002/(sici)1096-9896(199707)182:3<311::aid-path888>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytotoxic molecules in intestinal T-cell lymphomas

Abstract: Intestinal T‐cell lymphoma (ITCL) represents a subgroup of peripheral T‐cell lymphomas which is thought to arise from αβ intraepithelial T‐lymphocytes. Since these lymphocytes may contain cytotoxic molecules, the question of whether this also holds true for ITCL arises. Twenty ITCL cases were examined for the presence of granzyme B, perforin, and T‐cell‐restricted intracellular antigen (TIA‐1)/granule membrane protein of 17 kD (GMP‐17). Two molecules with restricted expression in cytotoxic cells, granzyme B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…2,3,6,7,16,21,25 The WHO classification describes both subtypes of EATL (type I and II) as tumors of intraepithelial T cells, with predominantly cytotoxic T-cell features of the ab phenotype. 11,27 However, a recent study has demonstrated that neoplastic lymphocytes in EATL type II are more commonly of the gd phenotype. 9 Although not commonly available, identification of the ab or gd phenotype would allow further classification of the neoplastic lymphocytes in canine intestinal T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6,7,16,21,25 The WHO classification describes both subtypes of EATL (type I and II) as tumors of intraepithelial T cells, with predominantly cytotoxic T-cell features of the ab phenotype. 11,27 However, a recent study has demonstrated that neoplastic lymphocytes in EATL type II are more commonly of the gd phenotype. 9 Although not commonly available, identification of the ab or gd phenotype would allow further classification of the neoplastic lymphocytes in canine intestinal T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, smaller cells in the duodenum had stronger CD56 expression than that of larger cells in the ileum (Figs. 10,11).…”
Section: Ihc and Ifmentioning
confidence: 99%
“…In addition, most of these neoplastic cells express CD30. EATL type 1 originates from cytotoxic IELs (CD8+ αβ intraepithelial T lymphocyte), as demonstrated by the cytotoxic phenotype of tumor cells, which are perforin+, granzyme B+, and TIA-1+ [ 117 , 118 ]. The phenotype mostly consists of medium- to large-sized tumor cells with round or angulated vesicular nuclei, prominent nucleoli, a pale-staining cytoplasm, and an increased mitotic index, which is often associated with moderate to abundant infiltration of eosinophils, histiocytes, and small lymphocytes [ 94 ].…”
Section: Celiac Disease and Lymphomasmentioning
confidence: 99%
“…ITCLs consistently express cytotoxic molecules which indicates their derivation from cytotoxic cells. 7,8 Therefore we were interested whether the same holds true for our GTCL cases. The ®ndings of these investigations suggest that GTCL may be heterogeneous in respect to the expression of these molecules.…”
Section: Discussionmentioning
confidence: 97%